Safety in Numbers: Cost-effective Endangered Species Management for Viable Populations. - Donovan, Pierce; Bair, Lucas S.; Yackulic, Charles B.; Springborn, Michael R. (Land Economics, 2019)
We develop a bioeconomic model to identify the cost-effective control of an invasive species (rainbow trout) to achieve a population viability goal for an endangered species (humpback chub) in the Grand Canyon of the U.S. Southwest. Solving the population viability problem is difficult since avoiding a threshold with a given confidence imposes a probabilistic restriction on joint outcomes (survival) over many periods. We develop a novel dynamic programming solution approach that is fast and forgoes the simulation method requirement of imposing structure on the policy function. We also investigate an adaptive management model that incorporates learning about uncertain biological dynamics. (JEL Q22, Q57)